(untitled) (SCIENCE TIME JOURNAL, 2026)
This article examines the interpretation of standard language, dialect and sociolect in theoretical linguistic literature. In modern linguistics, language is viewed not as a homogeneous and fixed system, but as a dynami social phenomenon shaped by history, territory, social structure and cultural identity. The study focuses on British English, where standardisation, regional variation and social differentiation are closely interconnected. Standard language is interpreted as a codified and institutionally supported variety used in education, administration, formal communication and written discourse. Dialect is described as a systematic variety with phonetic, lexical and grammatical features associated with a particular region or speech community. Sociolect is analysed as a variety connected with social class, profession, age or group identity. Particular attention is given to the distinction between Standard English and Received Pronunciation. The article concludes that dialects and sociolects are not inferior forms, but natural and socially meaningful language varieties.